S. Bianchetti, M. R. Cataudella & H.-J. Gehrke (eds.) Brill’s Companion to Ancient Geography. The Inhabited World in Greek and Román Tradition. Leiden-Boston, Brill, 2016, 512 pp. - Cano Ricárdez, Teresita (2018)
Fil: Cano Ricárdez, Teresita. Universidad Nacional Autónoma de México